High-throughput sequencing discovered diverse monopartite and bipartite begomoviruses infecting cucumbers in Saudi Arabia - Sattar, Muhammad Naeem; Almaghasla, Mostafa I.; Tahir, Muhammad Nouman; El-Ganainy, Sherif M.; Chellappan, Biju Vadakkemukadiyil; Arshad, Muhammad; Drou, Nizar (Frontiers in Plant Science, 2024)
Limited research in Saudi Arabia has devolved into the prevalence and genetic diversity of begomoviruses. Utilizing Illumina MiSeq sequencing, we obtained 21 full-length begomovirus sequences (2.7-2.8 kb) from eight cucumber plants grown in fields and greenhouses. We found that two complete begomovirus genomes were variants of the Boushehr strain of tomato yellow leaf curl virus (TYLCV) with nucleotide (nt) sequence identities of 94.7-95.9%. Another fulllength genome was a variant of TYLCV-Iran with 94.6% identity. Five full-length sequences closely matched the DNA-A of watermelon chlorotic stunt virus (WmCSV) isolates with 97.9-98.7% nt sequence identities, while five sequences had their highest nt sequence identities (95.8-96.3%) with the DNA-B of WmCSV isolates. Simultaneously, four sequences were 99.1-99.6% identical to the DNA-A of tomato leaf curl Palampur virus (ToLCPalV). Four sequences matched the DNA-B of ToLCPalV reported from Iran and Saudi Arabia with identities ranging from 96.2-100%. Four plants showed a mixed infection of these begomoviruses. Most ORFs showed evidence of negative selection pressure, suggesting that purifying selection plays a crucial role in shaping the diversity of these begomoviruses. Additionally, potential intra-and interspecies recombination events were detected in the TYLCV and WmCSV DNA-B genomic regions. The ToLCPalV isolates identified in this study formed a cluster with the other ToLCPalV isolates reported from Saudi Arabia, Iran and Iraq, representing a unique lineage distinct from ToLCPalV reported from Southeast Asia. High mutation rate and robust selection facilitated the independent evolution of ToLCPalV without recombination. Overall, this study offers valuable insights into the diversity and evolutionary dynamics of begomoviruses infecting cucumber crops in Al-Ahsa,